Kearifan Lokal Pengobatan Tradisional Masyarakat Desa OMU Kecamatan Gumbasa Kabupaten Sigi - Qodir, Abdul; Juraid (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2024)
This research aims to describe the local wisdom of traditional medicine in the OMU Village Community, Gumbasa District, Sigi Regency The problem of the research is: How is the local wisdom of traditional medicine that utilizes types of traditional medicinal plants, what are the forms of community participation in preserving traditional medicine. The type of research used is qualitative research using a descriptive approach to data collection techniques in the form of observation, instruments, interviews,, and documentation. The results of the research are that the people of Omu Village still believe in traditional medicine as local wisdom which is still maintained to this day. Some of the medicinal plants used to cure diseases are still classified as herbal, namely turmeric, papaya leaves, moringa leaves, sweet potatoes, jatropha leaves, soursop leaves, ginger, Javanese wood, tempting leaves, galangal,, and guava leaves. The parts of the plant used as medicine are 6 leaves (54.5%), 3 rhizomes (27.3%), 1 stem (9.1%), and bark (9.1 %).